The Mediation of Gratitude in the Relationship Between State Hope and Couple Burnout: A Dyadic Approach - Osmanoglu, Naile; Benzer, Miray Sariyildiz; Sarac, Humeyra; Ergin, Kemal Feyzi; Erus, Seher Merve; Satici, Seydi Ahmet (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
Romantic relationships are crucial to life, but disappointment and unmet expectations can lead to couple burnout. Gratitude, as a positive emotional response, serves as a protective factor in relationships. It was considered necessary to examine couple burnout, hope, and gratitude, in terms of positive psychotherapy. This study aimed to examine the actor-partner interdependence between state hope and couple burnout and to test gratitude as a mediator using an APIMeM approach. The study included 338 heterosexual couples (N = 676) from T & uuml;rkiye. Path analysis was conducted to evaluate actor, partner, and indirect effects. Results indicated that men reported higher state hope, whereas women reported higher gratitude and lower couple burnout. Across both genders, higher state hope was associated with higher gratitude, and higher gratitude was associated with lower couple burnout. Regarding partner effects, men's state hope significantly predicted women's gratitude, and women's gratitude significantly predicted men's couple burnout. In contrast, women's state hope did not predict men's gratitude, and men's gratitude did not predict women's couple burnout. Overall, gratitude emerged as a key mechanism linking state hope to lower couple burnout.
Keywords: Couple burnout; state hope; gratitude; dyadic approach; ROMANTIC RELATIONSHIPS; CONFLICT-MANAGEMENT; EMOTION WORK; JOB BURNOUT; GENDER; HAPPINESS; LOVE; SEX; Psychology